Short-term and long-term behavioral effects of vaccination mandates - Onur Baser; Katarzyna Rodchenko; Lu Chen; Nehir Yapar (Taylor & Francis Group, 2023)
ABSTRACTCurrent COVID-19 vaccination levels are insufficient to achieve herd immunity. To implement effective interventions toward ending the pandemic, it is essential to understand why people are motivated and willing to receive vaccination. The study aims to evaluate attitudes toward COVID-19 vaccination mandates and the impact of policies on future vaccine uptake and behavior utilizing self-determination theory. We conducted an online survey (n = 569) in the U.S. and Turkey to investigate a relationship between respondents' psychological needs and their willingness and motivation to receive COVID vaccination. The study examined the possible impact of vaccine mandates on these needs. Autonomy satisfaction was the leading predictor of willingness to receive vaccination (p < .0001). Relatedness satisfaction was the leading predictor of one's intention to receive vaccination (OR = 3.382; p = .0001). The strongest positive correlation was found between needs frustration and external motivation. A moderate positive correlation was found between competence frustration and introjected motivation. No association was found between vaccine mandates and psychological needs. Need satisfaction, especially autonomy and relatedness, appear to positively influence willingness and intention to receive a vaccination. On the other hand, need frustration, especially autonomy and competence frustration, correlates with external motivation, thereby suggesting a detrimental long-term effect on vaccination behavior. Need satisfaction promotes positive vaccination behavior, while need frustration might adversely affect motivation and willingness to receive vaccination. Strategies promoting autonomous decision-making might be more effective than vaccination enforcement in sustaining positive vaccination behavior.